![\frac{x + 5}{6} - \frac{x + 1}{9} = \frac{x + 3}{4} \frac{x + 5}{6} - \frac{x + 1}{9} = \frac{x + 3}{4}](https://tex.z-dn.net/?f=+%5Cfrac%7Bx+%2B+5%7D%7B6%7D++-++%5Cfrac%7Bx+%2B+1%7D%7B9%7D++%3D++%5Cfrac%7Bx+%2B+3%7D%7B4%7D+)
Answers
Answered by
1
.
➡Given here .
(x+5)/6 - (x+1)/9 = (x+3)/4
↪3(x+5)-2(x+1)=18(x+3)/4
↪3x-2x+15-2=1/2(9x+27)
↪x +13=1/2(9x+27)
↪2x+26=9x+27
↪9x-2x + 27-26=0
↪7x = -1
↪x = -1/7
Similar questions
Computer Science,
6 months ago
Accountancy,
6 months ago
Computer Science,
6 months ago
Math,
1 year ago
Biology,
1 year ago